In vitro digestion and bioaccessibility studies of vitamin E-loaded nanohydroxyapatite pickering emulsions and derived fortified foods - Ribeiro, Andreia (2022)
Vitamin E is a lipophilic vitamin playing an essential role in human health. Due to oxidative instability, it presents fast degradation and bioactivity loss. In this study, vitamin E-loaded Pickering emulsions stabilized by nano-hydroxyapatite (n-HAp) were produced using a static mixer (NETmix), a technique enabling continuous production and droplet size tailoring. Thus, oil-in-water (O/W) emulsions containing vitamin E at a content of 1mg/mL were produced with different droplet sizes (7.53, 11.56 and 17.72m) using an O/W ratio of 20/80 (v/v). Their stability during in vitro gastrointestinal digestion and vitamin E bioaccessibility were investigated. It was observed that n-HAp particles disrupt in the stomach and subsequently aggregate as random calcium phosphates in the small intestine, leading to low vitamin E bioaccessibility due to oil entrapment. The emulsion showing the highest vitamin E bioaccessibility (3.29±0.57%, sample with the larger average droplet size) was used to produce fortified gelatine and milk, resulting in an increased bioaccessibility (10.87±1.04% and 18.07±2.90%, respectively). This fact was associated with the presence of macronutrients and the lower n-HAp content. Overall, n-HAp Pickering emulsions offer advantages for vitamin E encapsulation directed to fortified foods development, a process able to be extended to other lipophilic vitamins.